PRESENT STATUS OF THE HIMALAYAN MAHSEER TOR PUTITORA, AN ENDANGERED SPECIES IN NAINITAL LAKES OF UTTAR PRADESH - PANDEY, K. D. (Journal of Indian Fisheries Association, 2006)
The present status of the. Himalayan m.ahseer in the three lab:es ofNainital district of U.P. is discussed based on the catch data from 1983-84 to 1992-93. Yield of mahseer have shown a gradual decline in the recentyears. Besides catch statistics, marlret arrivals and availability of fish toanglers have also shown a marked decline. Tor putitora is beingconsidered as an endangered fish. It is therefore necessary to repopulatethe lake9 with the mahseer by adopting better Inanagement practiceslike stocking the lakes continually with sufficient mahseer fingerlingsand enforce stdct conservation measures to stop killing of juveniles.